Landscape response to late Quaternary climatic change on the Southern High Plains, USA - Rich, J (2003)
﻿ Long-term palaeo-climatic conditions have primarily been interpreted from ocean marine sediments and ice cores. Few middle and low latitude continental records exist that provide insight into continental response to climate change over time. This research offers new chronologies on a variety of low latitude continental deposits from the Southern High Plains, and demonstrates their importance as palaeo-environmental archives. These chronologies extend the existing Southern High Plains palaeo-environmental record from the historic period to the late-middle Pleistocene, and provide an important basis from which to examine landscape response to late Quaternary climate change. This study demonstrates the applicability of optical dating procedures to well-bleached sedimentary features, such as lunettes, lacustrine material, tufa, and coversands. The precision and accuracy of the technique permits the detection of historic depositional events, whilst the range of the dating technique extended the chronology to the middle-late Pleistocene. The physical isolation of the Southern High Plains from its surrounding areas for the last 1.6 Ma has preserved a record of past climatic fluctuations within the aeolian and fluvio-lacustrine sediments. This research has demonstrated that the Southern High Plains landscape is sensitive to periods of less effective moisture, causing reactivation during historic drought periods (e.g. 1930s "Dust Bowl" event). Coversands and small playa lunettes were active during glacial and interglacials. This suggests that these features are sensitive to smaller scale climatic fluctuations that result in reduced effective moisture for the region during both glacial and interglacial periods. Large lake lunettes were inactive during the Wisconsin glacial. During this same period, active lacustrine and tufa deposition occurred; this offers evidence of greater effective moisture for the Southern High Plains, which resulted in regional recharge. The record of climate change preserved in the lunettes, lacustrine material, tufa, and coversands has provided insight into the response of this dynamic landscape to climatic fluctuations and has been employed for the reconstruction of the palaeo- environmental history of the Southern High Plains. An understanding of landscape response is important in light of the future of the Southern High Plains environment as global temperatures increase, and is critical to a complete evaluation of continental response to climatic change.